Answer:
Probability that the person preferred milk as his or her primary drink = 0.3
Step-by-step explanation:
Given -
In a recent survey, 18 people preferred milk, 29 people preferred coffee, and 13 people preferred juice as their primary drink for breakfast .
Total no of people is = 18 + 29 + 13 = 60
If a person is selected at random ,
The probability of person preferred milk =
The probability of person preferred coffee =
The probability of person preferred juice =
Probability that the person preferred milk as his or her primary drink =
P ( milk ) =
= = 0.3
2x+20=58 then your would subtract 20 from 58 which would turn into 38 and your would divide 38/2 it would be 19 so the answer is x=19 if I’m not mistaken this is correct hope this helps
Answer:
me either
Step-by-step explanation:
We are given the graph of sine function.
First, we get the amplitude
A = [6 - (-2)] / 2
A = 4
Next, we determine the period and b
T = 4 - 0 = 4
b = 2π / T
b = π/2
The original sine function was
y = 4 sin πx/2
After the transformation, the equation now is
y = 4 sin [π(x+2)/2] + 2
Answer:
Differentiation will give you the gradient for the tangent at any point, and you use the product rule whenever a function can be thought of as two functions multiplied together.
If
f
(
x
)
=
g
(
x
)
×
h
(
x
)
then
f
'
(
x
)
=
g
'
(
x
)
h
(
x
)
+
g
(
x
)
h
'
(
x
)
so if
y
=
x
×
sin
x
then
d
y
d
x
=
1
×
sin
x
+
x
×
cos
x
=
sin
x
+
x
cos
x
We know that
x
=
π
2
, so the gradient is
m
=
sin
(
π
2
)
+
π
2
cos
(
π
2
)
=
1
+
π
2
×
0
=
1
Therefore, we can say that
y
=
m
x
+
c
y
=
(
1
)
x
+
c
y
=
x
+
c
So all we really need to find now is the value for
c
, the
y
intercept. We do this by working out a point
(
x
,
y
)
on the graph. We are already given that
x
=
π
2
, so
y
=
x
sin
x
=
π
2
sin
(
π
2
)
=
π
2
×
1
=
π
2
∴
(
x
,
y
)
=
(
π
2
,
π
2
)
Now we substitute this into the equation we already have for the tangent,
y
=
x
+
c
,
(
x
,
y
)
=
(
π
2
,
π
2
)
π
2
=
π
2
+
c
c
=
π
2
−
π
2
=
0
∴
y
=
x
+
c
=
x
+
(
0
)
=
x
which means the tangent to the curve
y
=
x
sin
x
at
(
π
2
,
π
2
)
is simply
y
=
x
.